Sensitivity of ecosystem functioning to changes in the structure of soil food webs - Laakso, Jouni (1998)
The main objective of this thesis was to assess the functionally important features in the detrital food web of coniferous forest soil by studying the role of top-down influences and species composition of trophic groups in the functioning of the food web. I manipulated food web structure in microcosms containing defaunated humus and litter, a birch seedling infected with ectomycorrhizal fungi, and a diverse microbial community. The faunal composition was also manipulated under N-poor and N-enriched conditions to assess whether the outcome of trophic interactions is sensitive to the availability of N. The role of wood ant Formica aquilonia Yarr. in the soil food web and system functioning was studied using field samplings and manipulations of wood ant density. In the laboratory experiments the biomasses of microbivorous and microbi-detritivorous grazers were effectively controlled by their predators. The influence of animal grazers on microbial biomass and respiration was weak and predators of grazers could exert only a weak positive influence on microbial biomass and activity. Field studies revealed that wood ants are negatively associated with other invertebrate predators and - positively associated with earthworms. Feeding trials showed that earthworms have antipredatory defence against wood ants. However, the overall effect of wood ants on soil food web was weak outside the nest mounds. The presence of a diverse microbivore and microbi-detritivore community, and maintenance of nest mounds by wood ants increased species richness of soil fauna. N mineralisation, and plant growth and N uptake increased in the presence of microbivorous and detritivorous fauna but their predators generally had a weak influence on these processes. N-enrichment magnified the influence of food web structure on microbial biomass and plant N uptake, and modified the outcome of animal-microbial interactions. Wood ants did not influence N dynamics and plant growth outside the nest mounds. The weak propagation of top-down influences and high number of functionally redundant species suggest that ecosystem functioning is robust against changes in the structure of below-ground food webs.